The intention to use Islamic banking products and perceived impacts on financial inclusion: a study to measure Islamic financial literacy in Malaysia - Beh, Khang Shun; Chan, Weng Kit; Chin, Kitty Kai Xin; Leong, Wei Shan; Yap, Sook Hui (2021)
This research is aimed to investigate the intention to use Islamic banking products among Malaysians. The study examines the intention to use Islamic banking product by included the independent variables of attitude, epistemic value, perceived behavioural control, religiosity and subjective and social norm. The target respondent that included in this research project are all the Malaysia which are 18 years old and above with a total number of 400 sets of survey questionnaire. SmartPLS 3 is used to assist in our data analysis which had along with the discriminant validity, significant of variables, bootstrapping as well as the reliability test. The research project result concluded the independent variables towards the intention to use Islamic banking products among the Malaysian which are 18 years old and above. Some limitation and suggestions are included in the study to provide better idea for future researchers and even Islamic bank in Malaysia to enhance the intention of Malaysian in using Islamic banking product in Malaysia.